Understanding the experience of users of communication aids and applications through focus group discussions with people with aphasia and family members - Azevedo, Nancy; Le Dorze, Guylaine; Jarema, Gonia; Alary Gauvreau, Christine; Ogourtsova, Tatiana; Beaulieu, Stéfanie; Beaujard, Christel; Yvon, Marc; Kehayia, Eva (Frontiers in Communication, 2023)
The present study sought to identify the communication needs of persons with aphasia (PWA) and of their spouses, that could ultimately be addressed with current communication aids or applications (CA/A). Among users of CA/A we solicited their opinions and experiences with current CA/A. In contrast, among those not using CA/A, we explored why they did not use CA/A. A qualitative experiential research design was used through two in-person focus groups, one in English and one in French, at a large rehabilitation hospital in the Greater Montréal region (Canada). Participants' responses were recorded, transcribed and analysed. The thematic analysis that ensued allowed the identification of four main themes. The first theme reflects participants' observations and experiences when communicating with aphasia. The second theme regrouped responses related to successful communication with the help of CA/A. The participants' challenges and dissatisfaction with CA/A were grouped into the third theme. Lastly, a fourth theme included participants' general views about CA/A and their wishes for further development. Participants' experience with communication difficulties following aphasia and the barriers and potential facilitators to adoption of CA/A were brought to the forefront. They also highlighted those features necessary to ensuring functional uptake of CA/A by those who would benefit from it. Finally, the importance of providing training to the communication partner and sensitizing the public to the impact of aphasia on people's daily lives and on the potential benefits of using CA/A were raised as necessary future actions.